Efektivitas E-Modul PAI dan Budi Pekerti dalam Meningkatkan Minat Baca Siswa di Kelas VII SMP IT Ar-Rochman - Mumfaridil Anwar; Nur Rohmah Hayati; Prawidya Lestari (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2023)
This study aims to analyze the effectiveness of PAI e-modules and ethics in increasing students' reading interest and supporting and inhibiting factors for reading interest in e modules at SMP IT Ar-Rochman Salaman. This research included classroom action research (PTK). The subject of the study was a student of grade VII B SMP IT Ar-Rochman, Salaman for the 2022/2023 school year. The sampling technique uses purposive sampling techniques or certain considerations from researchers and is continued with random sampling with subject collection techniques that obtain high (upper), medium (middle), and low (lower) results. The research instruments used are the main instrument (the researcher himself) and supporting instruments (test questions, questionnaires, and interviews). The results showed that e-modules were effective in increasing students' reading interest. This is evidenced by the increase between the results of cycle 1 and cycle 2 tests, namely from a percentage of 92.22% to 99.26%, then from the results of the questionnaire students strongly agree that e-modules can increase students' reading interest by a percentage of 59.10%, and from the interview results, students are more interested in the learning process using e-modules than ordinary books. The factor that makes the interest in reading attractive is the learning process with e-modules, because students are more interested in things that are not monotonous, while the factor that inhibits students is reluctant to read books because books are packaged monotonously without being accompanied by interesting images, writing, and colors.